Activation and Inhibition of Soluble Guanylyl Cyclase by S-Nitrosocysteine: Involvement of Amino Acid Transport System L - Riego, Joseph A. (2009)
In this study the mechanism by which S-nitrosocysteine (CysNO) activates soluble guanylyl cyclase has been investigated. CysNO is the S-nitrosated derivative of the amino acid cysteine, and has previously been shown to be transported into various cell types by amino acid transport system L (L-AT). Here we show using both neuroblastoma and pulmonary artery smooth muscle cells, that CysNO stimulates cGMP formation at low concentrations, but this effect is lost at higher concentrations. Stimulation of cGMP accumulation occurs only after its transport into the cell and subsequent flavoprotein reductase-mediated metabolism to form nitric oxide (NO). Consequently, CysNO can be regarded as a cell-targeted NO releasing agent. However, CysNO also functions as an NO-independent thiol-modifying agent and can compromise cellular antioxidant defenses in a concentration-dependent manner. The observed biphasic nature of CysNO-dependent cGMP accumulation appears to be due to these two competing mechanisms. At higher concentrations, CysNO likely inactivates guanylyl cyclase through modification of an essential thiol group on the enzyme, either directly or as a result of a more generalized oxidative stress. We show here that higher concentrations of CysNO can increase cellular S-nitrosothiol content to non-physiological levels, deplete cellular glutathione (GSH) and inhibit cGMP formation in parallel. Although the inhibition of sGC by S-nitrosation has been suggested as a mechanism of nitrovasodilator tolerance, in the case of CysNO, it appears to be more a reflection of a generalized oxidative stress placed upon the cell by the non-physiological levels of intracellular S-nitrosothiol generated upon CysNO exposure.